O ensino de Ciências e a formação de conceitos científicos no 8º ano de uma escola pública de Manaus - Oliveira, Débora Regina Soares de (2019)
The present dissertation is part of the Research Line Education in science, cognition and curriculum of the Post-Graduate Program in Education and Teaching of Sciences in the Amazon - UEA. The research had as a research problem the following question: How does the formation of Scientific Concepts in the teaching-learning process occur in Natural Science classes in the 8th year of Elementary School? And as a general objective to analyze the relationship between the teaching and learning process of the contents of Natural Sciences and the formation of scientific concepts in the 8th year of elementary school. One (1) science teacher and thirty-nine (39) students from the 8th grade of elementary school, from a public school in Manaus (AM) participated in the study. As data collection techniques we used: semi-structured interview with the teacher, observation of the teaching-learning process and focus group with the students. The data were analyzed from the Historical-Cultural matrix proposed by Vygotsky, using the following categories of analysis: a) Scientific concepts in science teaching; b) Spontaneous concepts and contextualization in the process of forming scientific concepts; c) Difficulties pointed out by the teacher in the teaching-learning process of scientific concepts; d) Problems observed that hinder the formation of scientific concepts in science teaching; e) Indicators of the process of formation of scientific concepts. We analyze the contexts of the study, as well as the teaching activity in the classroom, in the interactive processes of the construction of scientific concepts. As a result it was possible to perceive that the students as well as the Teacher did not abandon their more primitive forms of thought, the thought by Complexes. We perceive that the teaching-learning process in the classroom presents with extreme complexity and difficulty, since many of the necessary aspects involved in the construction of the scientific concepts are not approached correctly in the classroom or even known by the teacher. Keywords: Formation of Scientific Concepts. Teaching-Learning. Science teaching. Historical-Cultural Theory.